Macular and Peripapillary Retinal Nerve Fiber Thickness in Unilateral Amblyopic Eye - Shrestha, Chunu; Rajbhandari, Reeta; Poudel, Manish (Nepal Medical College Journal, 2021)
Amblyopia is the most common cause of monocular visual impairment in both children, and young to middle-aged adults, affecting 2%–5% of the general population. The objective of this study was to compare the peripapillary nerve fiber thickness and macular thickness in amblyopic eyes, fellow eyes and normal control eyes using spectral domain optical coherence tomography. This was a cross-sectional observational study conducted at R M Kedia Eye Hospital, Birgunj, Nepal from February 2020 to July 2020. Pediatric patients with unilateral amblyopia (anisometropic amblyopia, strabismic amblyopia or both) among the age group of 6-18 years attending pediatric department of RM Kedia Eye Hospital were enrolled for the study. All patients underwent a full ophthalmological assessment, including visual-acuity testing, anterior segment evaluation with Topcon slit lamp and fundus examination with Volk +90D lenses. All statistical analysis was done in SPSS V. 20. The average peripapillary retinal nerve fiber layer thickness was 120.6 μm (SD=14.6 μm) in the amblyopic eye, 118.1 μm (SD=15.6 μm) in the fellow eye and 113.2 μm (SD=9.4 μm) in the normal eye (p=0.104) respectively. The average macular thickness was 298.6 μm (SD=19.1 μm) in the amblyopic eye, 296.9 μm (SD=11.2 μm) in the fellow eye and 303 μm (SD=12.4 μm) in the normal eye (p=0.260) respectively. In conclusion, our study did not find any significant difference in the peripapillary retinal nerve fiber thickness or macular thickness when compared between amblyopic eyes, fellow eyes, gender and age matched normal eyes.